REVITALISASI KELEMBAGAAN PROGRAM KB SEBAGAI UPAYA PENGENDALIAN LAJU PERTUMBUHAN PENDUDUK - S. Budi Prasetyo; Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
One of the main critical issues in a decentralized development today is the failure of family planning programs that are affected by its institutional forms. This study aims to develop a formula institutional revitalization of family planning program managers are required at this time. The method used in this research is descriptive qualitative models using Spradley’s analytical techniques. This research was conducted in Pekalongan Municipal, Wonosobo Regency, and Purworejo Regency. The conclusion of this study is that the deterioration of family planning programs in the area due to lack of commitment from local leaders, organizations do not focus in carrying out its functions, especially the field staff (field officers), lack of resources and synergies in the implementation of the program. Chief policy areas are very influential in determining the shape of the organization, resource allocation and implementation of synergies. Institutional revitalization needs to be done by the local government is established agencies that focus on population and family planning affairs so that the implementation in the field (field officers) are more focused on family planning matters, but on the other hand still have to pay attention to the ability of the region and some other matters. In addition to the organization in the form of focus, also need to be supported adequacy of resource allocation and increased synergy among sectors fostered by regional heads.